2015
DOI: 10.1371/journal.pone.0126580
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inhibition of PDE5 Limits Pro-Inflammatory Monocyte-Macrophage Polarization in Streptozotocin-Induced Diabetic Mice

Abstract: Diabetes mellitus is characterized by changes in endothelial cells that alter monocyte recruitment, increase classic (M1-type) tissue macrophage infiltration and lead to self-sustained inflammation. Our and other groups recently showed that chronic inhibition of phosphodiesterase-5 (PDE5i) affects circulating cytokine levels in patients with diabetes; whether PDE5i also affects circulating monocytes and tissue inflammatory cell infiltration remains to be established. Using murine streptozotocin (STZ)-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 47 publications
(55 reference statements)
2
42
0
Order By: Relevance
“…In line with these findings, relevant signs of ventricular dysfunction and the overt DCM phenotype occur in this model of late diabetes, as reported in previous studies [12,22]. Although we cannot exclude that other mechanisms, besides humoral changes, are involved [50], our data confirm that prolonged hyperglycemia induces M1 macrophage infiltration which is known to be associated with reduced survival and greater tissue damage [28,51]. RSV treatment promoted the M2 macrophage phenotype, resulting in a significant reduction in the M1/M2 macrophage ratio, accompanied by a recovery of cardiomyocyte ultrastructural properties.…”
Section: Discussionsupporting
confidence: 92%
“…In line with these findings, relevant signs of ventricular dysfunction and the overt DCM phenotype occur in this model of late diabetes, as reported in previous studies [12,22]. Although we cannot exclude that other mechanisms, besides humoral changes, are involved [50], our data confirm that prolonged hyperglycemia induces M1 macrophage infiltration which is known to be associated with reduced survival and greater tissue damage [28,51]. RSV treatment promoted the M2 macrophage phenotype, resulting in a significant reduction in the M1/M2 macrophage ratio, accompanied by a recovery of cardiomyocyte ultrastructural properties.…”
Section: Discussionsupporting
confidence: 92%
“…Chronic proinflammatory M1-type macrophage infiltration has been reported in insulin resistance linking diabetes to vascular disease: defective remodeling and repair following injury in diabetes are the final steps of an impaired control of inflammation and tissue damage. A recent study on murine streptozotocin-induced diabetes and in human vitro cell-cell adhesion models showed that sildenafil treatment (1.6 mg/kg/day for 3/6 weeks) was able to restore the endothelial cells alteration and proinflammatory status, hyperglycemia related, by reducing vascular inflammatory proteins, promoting tissue protection, and lowering monocyte adhesion to human endothelial cells [63].…”
Section: Possible Mechanisms and New Perspectives In The Cardiac Benementioning
confidence: 99%
“…PDE5 inhibitors (PDE5is) may have an active role in the management of DN13 by reducing glomerulosclerosis and proteinuria and improving vascular inflammation and podocyte count in experimental diabetes models14151617. These findings, together with the modulation of inflammatory1418 and angiogenic mediators, and endothelial function1920 in murine and human models, support the use of PDE5i to prevent complications of the diabetic kidney.…”
mentioning
confidence: 92%